Studies on challenges and opportunities for foreign direct investment in the automobile industry in India - Kumar, Avdhesh; Agarwal, Manoj (The Scientific Temper, 2023)
Direct investment by a foreign entity into a domestic company is known as a foreign direct investment (FDI). In this way, the concept of direct control sets this type of investment apart from foreign portfolio investment. The current study aims to find various challenges and policies regarding foreign direct investment in India. And its proposition in the development of the Automobile industry of India. For this specific purpose, “primary and secondary data collection methods” were used to find the appropriate data to analyze. A total of 110 people from the automobile industry manufacturers were taken using a random sampling method. India is taken as the study area. Using a quantitative study (questionnaire) with a descriptive method, all the data was analyzed using a regression model with the help of tools like Excel and SPSS (Statistical Package for the Social Sciences). The result from the analyzed data indicates a significant impact of FDI on “India’s Development of the Automobile Industry.” There is a significant impact of Government policies on FDI in India. There is a significant impact of FDI and Government policies on the Development of the Automobile Industry in India.